Party offices of corporators - Ghosh, Ayan (2023)
Over 128 years, the BMC building has been modified to make provisions for piped water, electrical fittings and other modern amenities. The usage of spaces has also changed as the municipality has expanded its way of functioning. For example, rooms on the ground floor have been converted to offices of political parties who send elected corporators to BMC.